When Local Governments Plan to Give Their Past a Future: A State-Wide Analysis of Heritage Strategy Documents in New South Wales (Australia) - Dirk H. R. Spennemann (Land, 2024)
The authorized heritage discourse sensu Smith asserts that cultural heritage, and in particular heritage places, can be managed for the benefit of present and future generations through appropriate measures of identification, protection and conservation. Comprehensive planning at the individual place as well as community/local government level is the backbone to good management if ad hoc decisions are to be avoided. While all local government authorities (councils) in New South Wales (Australia) are mandated to produce Local Strategic Planning Statements with a ten-year horizon that may include statements related to heritage management, some councils also promulgated dedicated heritage strategies. So far, the nature and comprehensiveness of such planning instruments have never been formally investigated. This paper provides a state-wide analysis of Local Strategic Planning Statements and council heritage strategies in NSW. The review shows that the priorities expressed in heritage strategies are often mundane, with none of the strategies expressing aspirational priorities or actions. The value of heritage to a community is assumed axiomatically, with very few heritage strategies expressing a vision for why heritage management is of community relevance. Only a few heritage strategies demonstrate how they, and their strategic priorities, are interlinked with other local, let alone state-level, strategies and policies. Very few of the documents provide evidence for the basis on which the strategies are founded, such as canvassing public opinion, situational analysis or projections of demographic, social, societal and economic trajectories based on strategic foresight. This review highlights much room for improvement. In a post-modernist age of alternative truths, where trust in governments is declining, it is imperative that local government heritage strategies be grounded in the community, offer transparency in how priorities are decided and, above all, provide a clear and aspirational vision for the role that cultural heritage shall play in the community.